2017
DOI: 10.1016/j.surge.2015.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative exercise training is associated with reduced respiratory infection rates and early discharge: A case-control study

Abstract: Available online xxxResults: The rate of RTI was only 16.6% in the exercise group and 43.3% in the control group (P ¼ 0.024). None of the cases or controls suffered from a DVT or PE. Median postoperative length of stay in the control group was 11 ± 7.5 days whereas in the cases it was 8.5 ± 5.00 days (P ¼ 0.049). The Borg subjective breathlessness score in the cases group showed a decline in the subjective breathlessness on postoperative day 4 (P ¼ 0.002).Conclusions: Early aerobic activity with a pedal exerci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 20 publications
0
17
0
1
Order By: Relevance
“…Stair climbing was not necessarily being prescribed as an intervention despite physiotherapists expecting patients to achieve it as a milestone. Respondents also indicated that cycle pedals are an uncommon intervention post-operatively despite Bhatt and colleagues [ 6 ] determining that early aerobic exercise through the use of cycle pedals halved the rate of respiratory infection and length of stay. This was, however, a small single-centre study that needs to be validated prior to translation into standard physiotherapy practice in upper abdominal surgery patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stair climbing was not necessarily being prescribed as an intervention despite physiotherapists expecting patients to achieve it as a milestone. Respondents also indicated that cycle pedals are an uncommon intervention post-operatively despite Bhatt and colleagues [ 6 ] determining that early aerobic exercise through the use of cycle pedals halved the rate of respiratory infection and length of stay. This was, however, a small single-centre study that needs to be validated prior to translation into standard physiotherapy practice in upper abdominal surgery patients.…”
Section: Discussionmentioning
confidence: 99%
“…There is no published consensus around the optimal assessment tool(s) to screen patients for risk of PPC development and/or to evaluate the effectiveness of physiotherapeutic treatment post-UAS. Similarly, consensus on intervention effectiveness is currently absent, with recent research unable to demonstrate any physiotherapy technique to be superior than another at preventing PPCs [ 6 ]. Physiological outcomes of deep breathing exercises (DBEx) are variable, with many concluding that a reduction in respiratory capacity occurs regardless of prophylactic DBEx treatment [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…After title, abstract and fulltext reviews using inclusion criteria, 14 354 articles were excluded, leaving 18 articles for analysis ( Figure 1). Of the included articles, 2 studies were prospective cohort studies; 30,31 1 was described as a case-control study, although it was a matched retrospective cohort study; 32 7 were retro spective cohort studies involving surgical patients; [33][34][35][36][37][38][39] and 7 were RCTs [40][41][42][43][44][45][46] with an additional study of a secondary analy sis of the randomized Medical Patients with Enoxaparin (MEDENOX) trial (Table 1). 47…”
Section: Resultsmentioning
confidence: 99%
“…46 A venous thromboembolism event was a secondary outcome in 7 studies. 31,32,37,39,42,43,45 The use of pharmacologic prophylaxis for venous thromboembol ism varied: 6 studies prescribed prophylaxis for all patients, 8 did not report prophylaxis use, 2 did not use prophylaxis and 2 had different regimens by group. The heterogeneity of studies regarding patient populations, pharmacologic prophy laxis and ambulatory interventions precluded the aggregation of data for metaanalysis.…”
Section: Researchmentioning
confidence: 99%
“…Using effective strategies to prevent PPCs is essential in high-risk patients. Some strategies have been proved beneficial in previous studies, such as smoking cessation [ 14 ] and inspiratory muscle training [ 15 , 16 ] before surgery; use of regional anesthesia [ 17 , 18 ], lung-protective ventilation (for patients who received general anesthesia) [ 19 , 20 ] and goal-directed fluid therapy [ 21 ] during surgery; as well as use of continuous positive airway pressure or noninvasive ventilation [ 22 , 23 ] and early exercise [ 24 , 25 ] after surgery. High-risk patients, such as those complicated with bronchial asthma, chronic obstructive pulmonary disease (COPD), pneumonia, left ventricular dysfunction and morbid obesity, tend to develop AHR during the perioperative period [ 26 28 ], which increase the risk of PPCs.…”
Section: Discussionmentioning
confidence: 99%